Sediment origins in the Catamayo-Chira Transboundary Basin: impacts on Poechos Reservoir capacity under ENSO influence - Dunin-Borkowski, Maria S.; Farías de Reyes, Marina; Asencio, Fausto W.; Reyes-Salazar, Jorge Demetrio; Ochoa-Cueva, Pablo (Frontiers in Earth Science, 2025)
The Poechos Reservoir, which began operations in 1976 with an initial water storage capacity of 885 hm3, has undergone severe sedimentation. By 2018, bathymetric surveys from the Chira–Piura Special Project (PEChP), the institution responsible for its operation and maintenance, reported an accumulated volume of 520 hm3, representing a 58.8% loss in storage. This situation raises concerns about long-term water security and sediment source dynamics. The present study aims to quantify the total mass and annual origin of sediment inflows to the reservoir. The study analyzed the Transboundary Catamayo–Chira Basin for the period 2001–2017, selected according to data availability: MODIS vegetation cover mosaics (available since February 2000), PISCOp precipitation datasets from SENAMHI (available until mid-2018), and annual reservoir bathymetries from PEChP (available until 2018). Sediment supply was estimated using the sediment delivery ratio (SDR) model implemented in the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST 3.13.0) software and validated against bathymetric measurements. Results show that the basin supplies an annual median of 6.91 × 106 t yr−1, a value consistent with 6.53 × 106 t yr−1, derived from bathymetric data for the same period. Eastern sub-basins dominated contributions, with Macará (2.34 × 106 t yr−1), Quiroz (1.98 × 10⁶ t yr⁻¹), and Catamayo (1.50 × 106 t yr−1) accounting for 84.3% of the load, while Alamor and La Solana contributed only 0.65 and 0.18 × 106 t yr−1, respectively. However, the 2017 El Niño–Southern Oscillation (ENSO) event altered this pattern: basin-wide supply surged to 34.92 × 106 t, with western sub-basins contributing more than half of the total, including a 57-fold increase from La Solana. These findings demonstrate that sediment supply is strongly controlled by climatic variability, with ENSO events shifting the spatial dominance of sediment sources. The predominance of eastern sub-basins under normal conditions contrasts with the episodic but extreme contributions from western sub-basins during El Niño. This highlights the need for adaptive management strategies that combine vegetation cover restoration with basin-wide monitoring, especially in semi-arid Andean systems where reservoir capacity is critical for water security.